Ceramic precursor-phthalonitrile hybrid with improved high heat resistance through constructing binary continuous phases. (November 2022) - Wang, Zi-long; Zheng, Kun; Xiong, Jing-yun; Xun, Li-jiao; Han, Yue; Guo, Ying; Ye, Li; Han, Wei-jian; Wang, Jun; Liu, Wen-bin; Zhou, Heng; Zhao, Tong
Graphical abstract: Abstract: Achieving organic–inorganic hybrids with improved heat resistance above 500 °C using inorganic materials as filler remains a challenge because inorganic constitutes could not form continuous inorganic phases in hybrids. Here, we obtained organic–inorganic phthalonitrile hybrids with increased heat resistance using ceramic precursor (SiBCN) as the inorganic source. The results showed that hybrids formed Si-O bond between phthalonitrile and the ceramic precursors. The carbon fiber reinforced composites of hybrids exhibited high glass transition temperatures (over 700 °C). The hybrid with 30 wt% SiBCN displayed a high temperature for losing 10 % weight (above 555.4 °C (N2 )), and high mass residue (over 75 % at 900 °C (N2 )). The improved heat resistance of the hybrid was originated from the continuous inorganic phases derived from the ceramic precursors delaying transfer and escape for the small molecules generated in the phthalonitrile resin at elevated temperature. Furthermore, the hybrid showed excellent high-temperature stability of thermal conductivity. The as prepared organic–inorganic hybrids could potentially replace ceramic-based materials in servicing temperatures ranging from 500−700 °C.